2018
DOI: 10.3892/mmr.2018.9186
|View full text |Cite|
|
Sign up to set email alerts
|

MicroRNA‑485 targets MACC1 and inhibits cervical cancer cell proliferation and invasion

Abstract: A large body of evidence has indicated that microRNAs (miRNAs/miRs) have essential roles in the development and progression of cervical cancer. Thus, miRNAs with dysregulated expression are potential biomarkers for cervical cancer diagnosis and prognosis. In the present study, expression levels of miR‑485 were detected in cervical cancer tissues and cell lines. The effects of miR‑485 overexpression on the proliferation and invasion of cervical cancer cells were determined with Cell Counting kit‑8 and Transwell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Authors further addressed that MACC1 overexpression favors tumor growth and promotes tumor metastasis in an athymic mice model. Multiple signal pathways such as various microRNA (29, 30), lncRNA (31, 32), circular RNA (33), and molecules such as deleted in breast cancer 1 (34), statin and rottlerin (35), have been observed in the regulation of MACC1 expression. Based on these findings, MACC1 as a potential valuable therapeutic target has been proposed.…”
Section: Discussionmentioning
confidence: 99%
“…Authors further addressed that MACC1 overexpression favors tumor growth and promotes tumor metastasis in an athymic mice model. Multiple signal pathways such as various microRNA (29, 30), lncRNA (31, 32), circular RNA (33), and molecules such as deleted in breast cancer 1 (34), statin and rottlerin (35), have been observed in the regulation of MACC1 expression. Based on these findings, MACC1 as a potential valuable therapeutic target has been proposed.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to the diagnosis and treatment of metastatic CC, researchers have studied cervical tissues and found a relationship between miRNAs and the diagnosis and treatment of metastatic CC. It was of interest to find that decreased miR-99a/b [90], miR-125a [139], miR-138 [75], miR-140-5p [85], miR-144 [66], miR-195 [127], miR-205 [88], miR-214 [91], miR-218 [96,133,148,167], miR-329-3p [57], miR-337 [68], miR-362 [94], miR-374c-5p [143], miR-375 [67], miR-377 [126], miR-379 [104], miR-485 [105], miR-486-3p [62], miR-638 [123], and miR-1297 [129] expression strongly correlate with tumor size, TNM stage, tissue pathology grade, International Federation of Gynecology and Obstetrics (FIGO) stage, lymph node metastasis, or distant metastasis in patients with CC. In addition, overexpressed miR-20a [31], miR-21 [168], miR-92a [118], miR-145 [79], miR-195 [166], miR-199b-5p [169], and miR-501 [51] closely correlate with histological grade, tumor diameter, overall survival (OS), progression-free survival (PFS), late FIGO stages, lymph node metastasis, or preoperative metastasis.…”
Section: The Role Of Hpv-related Mirnas In the Metastasis Of CCmentioning
confidence: 99%
“…miR-379 might act as a tumor suppressor in CC via negatively modulating V-crk avian sarcoma virus CT10 oncogene homolog-like (CRKL) [104]. miR-485, which is inversely associated with metastasis associated in colon cancer 1 (MACC1), was proven by Wang et al [105] to inhibit the invasion of CC cells. Finally, based on the miRNAs mentioned above, related signaling pathways can be seen in Figure 2.…”
Section: Vascular Endothelial Growth Factormentioning
confidence: 99%
“…Downregulation of this miRNA was associated with advanced stage of the disease and lymph node metastasis. It was also found that miR-485 may exert its tumor suppressive function in cervical cancer by directly targeting MACC1 and inhibiting the Met/AKT signaling pathway ( 148 ). Conversely, downregulation of miR-664 in UCC resulted in increased expression of the c-Myc oncogene and the cyclin D gene, in-turn resulting in reduced expression of BAX and active Caspase-3.…”
Section: The Role Of Ncrnas In Hpv-induced Uccmentioning
confidence: 99%